Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1149/2.0521414jes
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Electrode Oxygen Transport Kinetics Using Electrochemical Impedance Spectroscopy Combined with Three-Dimensional Microstructure Measurement: Application to Nd2NiO4+δ

Abstract: Oxygen reduction kinetic parameters -oxygen ion diffusion D δ , molar surface exchange rate O and surface exchange coefficient k -were determined for porous Nd 2 NiO 4+δ solid oxide fuel cell cathodes as a function of temperature and oxygen partial pressure by analyzing electrochemical impedance spectroscopy data using the Adler-Lane-Steele model. Electrode microstructural data used in the model calculations were obtained by three-dimensional focused ion beam-scanning electron microscope tomography. Cathodes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 49 publications
(95 reference statements)
2
22
0
Order By: Relevance
“…Recently, it has been shown that the oxygen surface exchange rate k and solid-state oxygen diffusion coefficient D * can be estimated for porous MIEC electrodes by using the ALS model 20 combined with electrode microstructural data. 27,28 As shown in Fig. 1, electrode EIS data could be modeled reasonably well by an equivalent circuit consisting of an inductor (L), an ohmic resistance (R) and a modified Gerischer element (GE).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Recently, it has been shown that the oxygen surface exchange rate k and solid-state oxygen diffusion coefficient D * can be estimated for porous MIEC electrodes by using the ALS model 20 combined with electrode microstructural data. 27,28 As shown in Fig. 1, electrode EIS data could be modeled reasonably well by an equivalent circuit consisting of an inductor (L), an ohmic resistance (R) and a modified Gerischer element (GE).…”
Section: Discussionmentioning
confidence: 89%
“…Based on oxygen nonstoichiometry, the oxygen vacancy fraction, χ v , and the thermodynamic factor, A 0 , were estimated to be 0.035 and 1.85, respectively. 27,32,33 With the above quantities known, and R G and t G determined from the EIS fitting shown in Fig. 1, k and D * are calculated from Eqs.…”
Section: Discussionmentioning
confidence: 99%
“…The excellent ECSA for Ni@GC-450 suggests that the annealing temperature has a great influence on the electrocatalytic efficiency resulting from the defects of graphitic nanocarbon shells and electrochemical conductivity. Electrochemical impedance spectroscopy (EIS) is further performed to elucidate the characteristics of the intrinsic interfacial charge transfer and charge transport kinetics at the interface of the electrode and electrolyte. , As the Nyquist plots illustrated in Figure b, the smallest charge-transfer resistance for Ni@GC-450 implicates the best HER kinetics and the fastest Faradaic process resulting from the high electrochemical conductivity created from the fast redox reaction. And, an equivalent circuit diagram (the inset of Figure b) was created to model the underlying HER process.…”
Section: Resultsmentioning
confidence: 99%
“…For this SrTiO 3 :Fe system their results suggested the presence of O 2 n − in the RDS with one electron transferred; further, if the bulk and surface defect concentrations share the same pO 2 dependence, those authors concluded that formation of O 2 2− by electron transfer or dissociation of O 2 2− is the most likely RDS under the measurement conditions. An important point from their work and that of others [46,47] is that the pO 2 dependence of the reaction rate in equilibrium alone may not be sufficient to identify the fundamental, detailed RDS, since many mechanisms can share the same equilibrium pO 2 dependence.…”
Section: Role Of Bulk Chemistrymentioning
confidence: 99%